INVESTIGATION OF HEAD AND BED MORTAR REGION EFFECT IN MICRO SCALE MODELLING OF MASONRY WALLS - Karaton, Muhammet; Canakci, Kagan (Yildiz Technical Univ, 2020)
In this study, the effectiveness on the micro-model analysis by finite element method of masonry walls of head and bed mortar region is investigated. 3 dimensional fixed smeared crack model is preferred for the nonlinear behavior of mortar and brick regions of the walls. Failure surface of William-Warnke model is used for cracking and crushing calculations. For numerical investigation, experimental results of the Eindhoven walls are selected. The base shear force-top displacement curve and the fracture zones obtained from the experimental results of these walls are used for the comparison of the numerical results. Mortar region in finite element model is discretized two different material as bed and head regions. The effects on the numerical solutions of the two different mortar material are evaluated with regard to different material strength and different shear stress transfer coefficients. The experimental and numerical results are compared in terms of maximum base shear force, threshold displacement values and the fracture zones. According to evidence obtained from numerical solutions, it is observed that closest results to experimental results are obtained for base shear force and threshold displacement. A ratio between tensile and compressive strength of the head and the bed mortar regions are proposed. Values for shear retention factors using in opening and closing cases of the cracking regions where occurred into the two mortar materials, are recommended.
Keywords: Eindhoven walls; micro modelling; fixed smeared crack model; shear retention factors; head and bed mortar regions